2005
DOI: 10.1017/s0022112005006804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the near-field tip vortex behind an oscillating wing

Abstract: The near-field tip-vortex flow structure behind an oscillating NACA 0015 wing was investigated at ${\hbox {{\it Re}}}\,{=}\,1.86 \times 10^{5}$. For attached-flow and light-stall oscillations, a small hysteretic property existed between the pitch-up and pitch-down motion, and many of the vortex flow features were found to be qualitatively similar to those of a static wing. For deep-stall oscillations, the wing oscillations imposed a strong discrepancy in contour shapes and magnitudes between the pitch-up and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 47 publications
4
30
0
Order By: Relevance
“…The merger of two like-signed vortices (e.g. Melander et al, 1988;Meunier and Lewecke, 2005) is accompanied by an increased circulation of the new merged object, compared with each of its components (the total circulation is conserved), and the increase in circulation of trailing vortices as they entrain vorticity from their surroundings has also been shown in the near wake of an oscillating wing (Birch and Lee, 2005).…”
Section: Far Wakes Miss Details Observable In Near Wakementioning
confidence: 99%
“…The merger of two like-signed vortices (e.g. Melander et al, 1988;Meunier and Lewecke, 2005) is accompanied by an increased circulation of the new merged object, compared with each of its components (the total circulation is conserved), and the increase in circulation of trailing vortices as they entrain vorticity from their surroundings has also been shown in the near wake of an oscillating wing (Birch and Lee, 2005).…”
Section: Far Wakes Miss Details Observable In Near Wakementioning
confidence: 99%
“…Velocity and pressure field measurements in the wake of an aircraft model are a valuable resource in predicting the performance characteristics of the aircraft (Spalart 1998b;Rossow 1999), as well as a means to investigate the more fundamental nature of vortex flows (see, for example, Bandyopadhyay et al (1991) and Phillips & Graham (1984)). However, single-point scans of vortex flows (such as the hot-wire and multi-hole pressure probe data of Beninati & Marshall (2005), Birch et al (2004), Birch & Lee (2005), Chow et al (1997) and Dacles-Mariani et al (1995), to list but a few) will tend to underpredict vortex strength owing to the smoothing effect of vortex 'meandering', or the random, low-frequency modulation in the trajectory of the vortex centre. While a number of schemes have been proposed to correct single-point scans of vortex wakes for the effect of meandering (such as those of Devenport et al (1996), Bailey & Tavoularis (2008) and Iungo et al (2009)), it has also been shown that, with meandering amplitudes which are large but within the range of those observed experimentally, the reconstruction of the vortex velocity field from point measurements becomes impossible (Birch 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Note that C j = 0 identically for the hole registering the largest pressure. These definitions are based upon the same reasoning used to obtain (1) and (3): that the error in the approximations of local stagnation and static pressure will become velocity-independent when normalized against the approximation of local dynamic pressure. The pressure coefficients defined above have the advantages of being continuous throughout the range of calibration, and of being independent of the hole arrangement and the probe tip geometry.…”
Section: B Generalized N-hole Probe Calibration Algorithmmentioning
confidence: 99%
“…Furthermore, because they can provide local measurements of the three components of fluid velocity as well as of the local static and total pressure, they are of particular use in wake surveys (see [1,2,3,4] and references cited therein), for which optical methods may present difficulties owing to the potential flow interference arising from particle injection [5] and particle momentum effects [6].…”
Section: Introductionmentioning
confidence: 99%